Power evaluation of the influence of roughness on the value of contact stress for interaction of rough cylinders - Kravchuk, A.S. (Archives of Mechanics, 1998)
The paper deals with mathematical modelling of contact interaction of rough cylindrical bodies, what significantly reduces the complexity of investigation of contact stress in practice. The contact problem for a rough elastic disk and isotropic plate with a rough cylindrical hole has been considered. The explicit approximate solution of the integral equation is presented in this paper. It allows us to determine the influence of the rough layer characteristics on the distribution of contact stresses.